Agreement in diagnosing occupational asthma by occupational and respiratory physicians who report to surveillance schemes for work-related ill-health. Issue 7 (12th November 2009) - Turner, Susan; McNamee, Roseanne; Roberts, Catherine; Bradshaw, Lisa; Curran, Andrew; Francis, Mandy; Fishwick, David; Agius, Raymond
Abstract : Objectives: To assess diagnostic agreement for occupational asthma, and to identify case and rater characteristics associated with this diagnosis. Methods: Summaries of possible occupational asthma cases were sent to 104 occupational and respiratory physicians. Raters assigned likelihood scores (0–100%) of occupational asthma based on case histories (phase 1), and on histories plus investigative procedures (phase 2). Interclass correlation coefficients were calculated as statistical measures of reliability for occupational asthma scores. Comparisons between mean scores were assessed for statistical significance using tests based on multilevel models. RRs were calculated to summarise effects of raters' demographics, and of supplying investigative procedures information. Results: Occupational asthma scores showed limited agreement within each group of (occupational or respiratory) physicians, but scores were not systematically different. The difference between mean overall scores was 2.1% (52.1% occupational physicians; 50.0% respiratory physicians) in phase 1 (95% CI −2.6 to 6.8, p=0.37). In phase 2, mean overall scores were 46.1% (occupational physicians) and 41.5% (respiratory physicians); the difference in mean overall scores was 4.6% (95% CI −3.5 to 12.5, p=0.27). Raters with General Medical Council registration ≥1986 were more likely to give a positive occupational asthma diagnosis. In phase 2, male raters were more likely to label cases as occupational asthma than female raters (RR 4.5, 95% CI 3.3 to 6.0). Conclusions: The RR of a positive occupational asthma diagnosis was unaffected by clinical speciality. Further work on why physicians consider cases to be occupational asthma will assist better diagnosis and prevention of this disease.